Butterflies (Lepidoptera: Papilionidae) of two collections from Santander, Colombia - VILLALOBOS-MORENO, ALFONSO; CÉSPEDES-MANCILLA, JUAN CARLOS; AGUDELO-MARTÍNEZ, JUAN CARLOS (Revista Colombiana de Entomología, 2012)
A total of 153 individuals of the family Papilionidae deposited in the entomological collections of the Cor- poración de Defensa de la Meseta de Bucaramanga and the Universidad Industrial de Santander were revised. In the first one, 61 specimens were found and in the second one, 92 specimens were found. Eight genera, 18 species and 19 subspecies were identified. Descriptive analyses were made about altitudinal and geographical distribution.